-(67r+67s-94)=

Simple and best practice solution for -(67r+67s-94)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(67r+67s-94)= equation:


Simplifying
-1(67r + 67s + -94) = 0

Reorder the terms:
-1(-94 + 67r + 67s) = 0
(-94 * -1 + 67r * -1 + 67s * -1) = 0
(94 + -67r + -67s) = 0

Solving
94 + -67r + -67s = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-94' to each side of the equation.
94 + -67r + -94 + -67s = 0 + -94

Reorder the terms:
94 + -94 + -67r + -67s = 0 + -94

Combine like terms: 94 + -94 = 0
0 + -67r + -67s = 0 + -94
-67r + -67s = 0 + -94

Combine like terms: 0 + -94 = -94
-67r + -67s = -94

Add '67s' to each side of the equation.
-67r + -67s + 67s = -94 + 67s

Combine like terms: -67s + 67s = 0
-67r + 0 = -94 + 67s
-67r = -94 + 67s

Divide each side by '-67'.
r = 1.402985075 + -1s

Simplifying
r = 1.402985075 + -1s

See similar equations:

| 2x+8=-24 | | 5+14-2w=9-(4w+2) | | 45+0.20m=66 | | 11x-4=56-x | | 25.24=5x+3.89 | | 4(x+15)=60 | | 2x-(3y+4z)= | | 117=-39x | | 12n+4-5n=42 | | 2z^2-9z-5=0 | | 42.55+0.20m=90 | | 4w-1=5w+37 | | -8=3(-x+2)-x | | 16+5a=13a | | 1-2r=8-3r | | 48(x^3)+27x(y^2)+16(x^2)y-9(y^3)=0 | | x^2+0.4x-0.3=0 | | 12n-(14m-8m)= | | 3-2y=15+14y | | 8n-(n+3)=9 | | 48(x^3)+27x(y^2)+16(x^2)y-9(y^2)=0 | | 5x-5+7x=17 | | 3x+2(x-6)=3 | | 96=600(.04)t | | -3x+=-54 | | 8+p=2p+3 | | X=log-25 | | 0.4x+0.7(x-3)= | | 66-5x=4x+18 | | -4x-4y=28 | | 2n^2-9n-18=0 | | -4m+=-15 |

Equations solver categories